Downregulation of fascin in the first trimester placental villi is associated with early recurrent miscarriage - Lamptey, Jones; Li, Fangfang; Adu-Gyamfi, Enoch Appiah; Chen, Xue-Mei; Czika, Armin; Otoo, Antonia; Liu, Tai-Hang; Wang, Ying-Xiong; Ding, Yu-Bin (Experimental cell research, 2021)
Inadequate trophoblast proliferation, shallow invasion and exaggerated rate of trophoblast apoptosis are implicated in early recurrent miscarriage (ERM). However, the mechanistic bases of this association have not been fully established. We aimed at investigating the involvement of fascin, an actin-bundling protein, in trophoblast activities and ERM. We found that fascin was downregulated in the cytotrophoblasts (CTBs) and distal cytotrophoblasts (DCTs) of ERM placentae. Knockdown of fascin altered cellular and nucleolar morphology, and inhibited the proliferation but increased apoptosis of trophoblastic HTR8/SVneo cells. Furthermore, fascin knockdown decreased the expression of transcription factors such as Snail1/2, Twist and Zeb1/2, mesenchymal molecules such as Vimentin and N-cadherin, and the protein expression of phosphorylated extracellular signal-regulated kinase 1/2 (ERK1/2) and phosphorylates signal transducer and activator of transcript 3 (STAT3). Exposure of HTR-8/SVneo cells to hypoxia reoxygenation (H/R) decreased fascin expression to affect the cells’ invasion. Our results indicate for the first time that the downregulation of fascin is involved in the pathogenesis of early recurrent miscarriage; and hence a potential therapeutic target against the disease. •Fascin is downregulated in the placentae of pregnancies complicated by early recurrent miscarriage.•Knockdown of fascin decreased HTR-8/SVneo cells' proliferation, migration and invasion.•Fascin knockdown decreased phosphorylated ERK1/2 and phosphorylated STAT3 protein level in HTR-8/SVneo cells.•Hypoxia reoxygenation decreased fascin, N-Cadherin and Vimentin protein levels to affect HTR-8/SVneo cells' invasion.